Assessment Of General Competences In The Professional Development Of Foreign Language Teachers - Estrada, Lucía (Íkala, Revista de Lenguaje y Cultura, 2009)
This paper presents the results of the second phase of the research project ''Prácticas evaluativas en la adquisición de lenguas extranjeras, PEALE'' (Assessment practices in foreign languages acquisition), mainly oriented to propose an evaluation system where the communicative competences (linguistic, sociolinguistic and pragmatic) play a very important role. The fndings reveal a set of competences not yet openly discussed: the general competences, regarded by scholars from different academic backgrounds as key factors that deeply infuence foreign language (FL) learning, teaching, and assessment processes. The general competences (i.e., learning, learning to be, learning to do and learning to learn) are part of the teachers' profle proposed in different FL teaching training programs in Colombia. Therefore, it is important to refect on the consolidation processes of these competences: both on their incidence in the students' promotion process, and on the proper use of these competences in the FL teachers' performance and professional development. Teacher training is expected to provide teachers with the appropriate tools to develop the general competences in their actual academic performance contexts. However, the strategies are yet to be defned to verify whether the general competences are consolidated with teaching practice or they tend to lose visibility in favor of the linguistic competences. Received: 17-02-09 / Accepted: 08-06-09 How to reference this article: Estrada, L. (2009). Assessment of General Competences in the Professional Development of Foreign Language Teachers. Íkala. 14(2), pp.153-180.